2023
DOI: 10.1021/acsanm.3c01475
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Conductivity and Performance in Electrorheological Fluids Using a Nanosilica Grafting Approach

Erika Pavlikova,
Tomas Plachy,
Michal Urbanek
et al.

Abstract: Carbonization is considered an effective process for the preparation of carbon-rich solids for various applications. Raw carbonaceous particles however often possess high electrical conductivity, limiting their applicability in electrorheology. To address this drawback, the carbonaceous particles prepared from glucose through hydrothermal synthesis, followed by thermal carbonization in an inert atmosphere, were subsequently coated by compact and mesoporous nanosilica, giving rise to semiconducting particles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Among these, particular attention has been given to exploring the particle morphology effect [6,7], such as sphere-like [8], core-shell-like [9][10][11][12], rod-like [13], plate-like [14], bowl-like [15], etc. [16]. Asano et al reported one of the earliest experiments about utilizing elongated rod-shaped particles as ER particles [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, particular attention has been given to exploring the particle morphology effect [6,7], such as sphere-like [8], core-shell-like [9][10][11][12], rod-like [13], plate-like [14], bowl-like [15], etc. [16]. Asano et al reported one of the earliest experiments about utilizing elongated rod-shaped particles as ER particles [17,18].…”
Section: Introductionmentioning
confidence: 99%